(untitled) (Economics and region, 2021)
It is known that the labor intensity of procurement works is almost half of the total labor intensity of the production of mechanical engineering products and has a serious impact on the formation of the cost of the product. Therefore, the correct choice of the method of their production and the determination of the geometric parameters of the work pieces in the initial stages of design are important steps aimed at reducing the cost of parts and increasing the economic efficiency of production. The article deals with the problem of risk assessment in the design of procurement production. The classification of risk assessment methods based on the completeness of information is given, the essence of the methods of simulation modeling, statistical method, sensitivity analysis method, expert method and approach based on the use of fuzzy logic is presented. The developed fuzzy production model and decision support system allows investment and construction projects to plan actions to reduce the risk of projects by analyzing situations at the pre-project stage of production.